Communication Ethics of Medan Journalists In Implementing The Tabayyun Attitude In The Digital Era (Islamic Education Communication Perspective) - Arianda Tanjung; Syukur Kholil; Erwan Efendi (Edukasi Islami : Jurnal Pendidikan Islam, 2023)
This research analyzes the communication ethics of Medan journalists in implementing the tabayyun attitude in the digital era (Islamic communication perspective). Problems, supporting and inhibiting factors, and the impact of implementing communication ethics in implementing the tabayyun attitude in the digital era This research uses a descriptive method. Medan journalists as research informants were selected using a purposive sampling method of eight people with the status of members and administrators of PWI North Sumatra and AJI Medan. The research results show that the communication ethics of Medan journalists in the digital era are very important to be implemented in strengthening and making the implementation of the tabayyun attitude a success as a series of journalistic tasks carried out. Journalists in Medan are aware of the importance of the tabayyun attitude in carrying out their journalistic duties. However, the challenges faced by journalists in this digital era make implementing the tabayyun attitude more difficult and cause problems in the field. The problem that Medan journalists often experience is that they are required to present comprehensive news but still experience high time pressure (deadlines) from the press company where they work. Several supporting and inhibiting factors were found for Medan journalists in implementing the tabayyun attitude in the digital era. supporting factors: quality of resources (educational factor), experience in the world of journalism, ability to carry out journalistic tasks, and commitment to implementing the Journalistic Code of Ethics. Meanwhile, the inhibiting factors that are often experienced are high time pressure (deadlines), not having the intention to confirm, and not being skeptical about the information obtained. The impact of implementing the tabayyun attitude by journalists in the digital era was also found. By implementing a tabayyun attitude, journalists in Medan will be more careful in verifying any information before publishing it. This will have a positive impact on the credibility of the media they represent. The public will have more confidence in news presented by media that is trusted and has a good reputation for conveying correct and accurate information.